Evaluating the Role of Nutrient Competition in Debaryomyces hansenii Biocontrol Activity Against Spoilage Molds in the Meat Industry - Helena Chacón-Navarrete; Ignacio García-Álvarez de Toledo; José Ramos; Francisco Javier Ruiz-Castilla (Journal of Fungi)
The rejection of chemical preservatives reflects the growing demand for natural and safe products. This concern has spurred scientific interest in yeasts as biocontrol agents, given their antagonistic activity against undesired fungi, which is one of the main problems associated with preservative reduction. Debaryomyces hansenii is a non-conventional yeast that has shown great potential for inhibiting filamentous fungi in the food industry. This study investigated the role of nutrient competition in the biocontrol activity of D. hansenii against unwanted molds. Potentially pathogenic molds from spoiled food were isolated using different media and identified using Sanger sequencing. The inhibitory effects of different autochthonous D. hansenii strains under varying nutrient conditions were assessed against isolated molds using semipermeable membranes. Inhibition activity was measured by assessing mycelial expansion and spore production using image software analysis and classical cell counting using a Neubauer chamber. The results indicated that D. hansenii effectively inhibited mold growth and sporulation, with the autochthonous strains LR2 and SRF1 showing higher inhibitory activity than the control strain CBS767. The effectiveness of inhibition varied with the yeast–mold combination, highlighting the need for a species-specific analysis. Nutrient competition plays a complementary role in D. hansenii biocontrol but does not directly impact overall inhibition. This suggests that other mechanisms, such as direct cell interactions or metabolite production, may be crucial. These findings enhance our understanding of the potential of D. hansenii as a natural preservative and advance biocontrol methods for food safety.